ITAIPU: 50-YEAR TREATY (Interdisciplinary Studies Journal, 2025)
This article aims to discuss aspects of the Itaipu Treaty, which is 50 years old. According to Annex C, a review of the financial basis of the energy supply tariff is required. Methodologically, a timeline of Brazilian foreign policy, tensions and conflicts arising from the bilateral relationship with Paraguay and border issues was sought. With regard to theoretical bases, the production on border demarcation treaties was used. Finally, we highlight the importance of a review of the diplomatic implications that come into friction when it comes to borders.
Keywords: Treaty; Brazilian Foreign Polic; Border